2017
DOI: 10.1021/acs.jnatprod.6b01141
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents and Anti-inflammatory Principles from the Fruits of Forsythia suspensa

Abstract: Fifty compounds were isolated from the fruits of Forsythia suspensa, including 13 new compounds characterized as eight new diterpenoids (1-8), three new lignans (9-11), a new iridoid (12), and a new triterpenoid (13). Their structures were established on the basis of spectroscopic and spectrometric analysis. Most of the isolated compounds were examined for their anti-inflammatory activity in vitro. The results showed that several compounds displayed significant inhibition of fMLP/CB-induced superoxide anion ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Although the potency of the lignans exhibiting anti-inflammatory activity in this study was similar to bioactive lignans described in the literature [ 42 ], it is worth noting that most of the lignans with anti-inflammatory activity in this study have not been reported previously. Besides, there are no anti-inflammatory medicines act via inhibiting superoxide anion and neutrophil elastase.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Although the potency of the lignans exhibiting anti-inflammatory activity in this study was similar to bioactive lignans described in the literature [ 42 ], it is worth noting that most of the lignans with anti-inflammatory activity in this study have not been reported previously. Besides, there are no anti-inflammatory medicines act via inhibiting superoxide anion and neutrophil elastase.…”
Section: Discussionsupporting
confidence: 74%
“…Besides, butanolides and lignans were major skeletons in this study. Bioactivity results indicated that lignans could reduce superoxide anion generation in fMLP/CB-stimulated human neutrophils, and the anti-inflammatory activities of those compounds were as potent as compounds in the literature [ 42 ]. Furthermore, the structure-activity relationship (SAR) discussion of anti-inflammatory activity compounds indicated that furofuran lignan with methylenedioxy was the most active structure.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 4 , two iridoids ( 121 – 122 ), nineteen diterpenoids ( 123 – 141 ) and twenty-seven triterpenoids ( 142 – 168 ) have been confirmed in Forsythiae Fructus . Most of them were reported by Kuo et al [ 38 ] in 2017. The triterpenoid fraction contains eleven tetracyclic triterpenoids ( 142 – 152 ) and sixteen pentacyclic triterpenoids ( 136 – 151 ).…”
Section: Phytochemistrymentioning
confidence: 99%
“…Forsythia suspensa (F. suspensa) exhibits anti-bacterial, anti-inflammatory, antioxidant, anti-allergy, anti-virus and anti-cancer effects [2]. So far, more than 230 compounds have been separated and identified from F. suspensa [2], including phenylethanoid glycosides [3], flavonoids [4], triterpenoids [5], lignans [6] and other compounds. Phillygenin (PG), a bisepoxylignan compound [7], is one of the major ingredients in F. suspensa and has been used as a marker for the quality control of F. suspensa in several studies.…”
Section: Introductionmentioning
confidence: 99%